PENGARUH PEMBACAAN SURAT YASIN FADILAH TERHADAP PERILAKU MASYARAKAT: Studi Living Quran di Yayasan PATWA Kabupaten Cirebon - Sri Rahayu; Didi Junaedi; Umayah Umayah (Diya Al-Afkar: Jurnal Studi al-Quran dan al-Hadis, 2019)
At-Tarbiyyatul Wathoniyyah Islamic Boarding School (PATWA) located in the village of Mertapada Kulon, Astanajapura District, Cirebon Regency, is one of the Islamic boarding schools that conducts a routine reading of Surah Yasin, or commonly known as Surah Yasin Fadilah, in which there are dhirk and prayers. The phenomenon was used as the object of this study with some research questions formulated, which are (1) why do they conduct a routine reading of Surah Yasin Fadilah?, (2) what is the purpose of reading Surah Yasin Fadilah?, and (3) how does the practice of reading Surah Yasin Fadilah affect the community?